Lactuca tatarica (Asteraceae) in embryonic dunes on Wolin Island (NW Poland) - W. A., Wojciech Kowalski; Łysko, Andrzej; Popiela, Agnieszka (Biodiversity: Research and Conservation, 2015)
By the end of the 19th century, Lactuca tatarica was reported for the first time from an adventive occurrence on the North Sea and Baltic Sea coasts. In Wolin Island, the species has become established in the natural habitat and is clearly spreading in recent years. The community with L. tatarica was studied currently on the western point of Wolin Island along the stretch between the mouth of the Świna (Swine) River and a newly constructed breakwater of the external harbour. The taxon occupies relatively low parts of the sandy elevations of dune ridges, in patches of the Honckenyo-Agropyretum juncei association (habitat 2110). Furthermore, L. tatarica has been reported in recent years from some locations in Świnoujście (Usedom (Uznam) Island), Międzyzdroje, Wisełka and Międzywodzie.